PENDIDIKAN SARAPAN SEHAT MENUJU BANGSA SEHAT BERPRESTASI BAGI ANAK SEKOLAH DASAR NEGERI MAUK III KABUPATEN TANGERANG BANTEN - Ronitawati, Putri; Sa’Pang, Mertien; Sitoayu, Laras; Nuzrina, Rachmanida; Melani, Vitria; Dhyani S, Prita; Novianti, Anugerah (Jurnal Pengabdian Masyarakat AbdiMas, 2018)
AbstractIn the 6-12 year period, school-aged children are very sensitive in shaping their cognitive development. If during this period they experience hunger then the opportunity to study in school to be reduced (WFP 2006). One message Balanced Nutrition (message six), based on Permenkes No. 41/2014 is a habit of breakfast. Nutrition education accompanied by the provision of food in schools such as a healthy breakfast will run more effectively when walking in tandem. Healthy breakfast education activity aims to raise public awareness, especially school children about the importance of breakfast, the benefits of breakfast, the type of healthy breakfast, and snacks safe. This activity is held in order to commemorate World Health Day and National Education Day and aim to socialize healthy breakfast education activity for School Children at SDN Mauk III of Tangerang Regency of Banten. Socialization is done by providing nutrition education with comic media "Come Breakfast" as one of education media which accompanied by healthy breakfast together in class as much as 268 School Children attend and follow this activity with good Understanding and socialization is strengthened by education media and practice directly related healthy breakfast together in accordance with Balanced Nutrition used and given to the participants so easily understood and applied in everyday life both at home and at school. Such activities are important every year with different target targets, so that the socialization of healthy breakfast in accordance with the principles of balanced nutrition with nutrition education can be achieved well.Â Keywords: primary school children, nutrition education, healthy breakfastÂ AbstrakPada periode 6-12 tahun, anak usia sekolah sangat sensitif dalam membentuk perkembangan kognitifnya. Bila pada periode ini mereka mengalami kelaparan maka kesempatan untukbelajar di sekolah menjadi berkurang(WFP 2006).Salah satu pesan Gizi Seimbang (pesan keenam), berdasarkan Permenkes No 41/2014 adalah biasakan sarapan.Pendidikan gizi disertai penyelenggaraan makanan di sekolah seperti Sarapan sehat akan berjalan lebih efektif bila berjalan beriringan. Kegiatan pendidikan sarapan sehat bertujuan meningkatkan kesadaran masyarakat khususnya anak sekolah mengenai pentingnya sarapan, manfaat sarapan, jenis sarapan sehat, dan jajanan aman. Kegiatan ini dilaksanakan dalam rangka memperingati Hari Kesehatan Dunia dan Hari Pendidikan Nasional serta bertujuan untuk Â mensosialisasikan kegiatan pendidikan sarapan sehat bagi Anak Sekolah di SDN Mauk III Kabupaten Tangerang Banten. Sosialisasi dilakukan dengan memberikan pendidikan gizi dengan media komik âAyo Sarapanâ sebagai salah satu media edukasi yang disertai dengan sarapan sehat bersama di kelas sebanyak 268 Anak Sekolah hadir dan mengikuti kegiatan ini dengan baikÂ  Pemahaman dan sosialisasi diperkuat dengan adanya media edukasi serta praktek secara langsung terkait sarapan sehat bersama sesuai dengan Gizi Seimbang yang digunakan serta diberikan pada peserta sehingga mudah dipahami dan diaplikasikan dalam kehidupan sehari-hari baik di rumah maupun di sekolah. Kegiatan seperti ini penting dilakukan setiap tahun dengan target sasaran yang berbeda-beda, sehingga sosialisasi sarapan sehat sesuai dengan prinsip gizi seimbang yang disertai pendidikan gizi dapat tercapai dengan baik.Â Kata kunci : anak sekolah dasar, pendidikan gizi, sarapan sehat